Chemical Kinetic Mechanism for Pyrolysis Bio-oil Surrogate - Alviso, Dario (2018)
Bio-oil is a complex real fuel, considered as a carbon-neutral alternative to hydrocarbons in the transport sector, which is composed of hundreds of compounds, mostly oxygenated. Pyrolysis oil has high acidity, low thermal stability, low calorific value, high water content, high viscosity, and poor lubrication characteristics. Therefore, its use in transportation is limited. These characteristics make it totally different from petroleum fuels affecting the combustion process. Blends of bio-oil/diesel/alcohols are viable short-term alternatives to utilize an important fraction of these oils. In the present work, pyrolysis was performed on torrefied coconut endocarp and the collected bio-oil was analyzed using gas chromatography/mass spectrometry (GC/MS). Based on the GC/MS analysis, three different blends of toluene, ethanol, and acetic acid representative of the real fuel chemistry were proposed as the surrogates to carry out combustion studies. The objective of this paper is to develop a chemical kinetics mechanism for toluene/ethanol/acetic acid blend oxidation. This will be done by combining the chemical model of Huang et al. [Energy Convers. Manage. 2017, 149, 553] for toluene and that of Christensen and Konnov [Combust. Flame 2016, 170, 12] for ethanol/acetic acid reactions. The resulting chemical model consisting of 180 species and 1495 reactions will be validated by performing combustion zero- and one-dimensional simulations for toluene/ethanol/acetic acid blends by studying constant-volume autoignition and laminar flame speed. Then, as Huang et al.'s original model was developed and validated for diesel/n-butanol blends, autoignition delays and laminar flame speed simulations of bio-oil/diesel/n-butanol are presented.